Greenhouse gas emissions patterns and insertion in global value chains: a comparative study between Brazil and China (2000–2016) - Tiago Ferreira Barcelos; Kaio Glauber Vital Costa (EconomiA, 2024)
Purpose – This study aims to analyze and compare the relationship between international trade in global value chains (GVC) and greenhouse gas (GHG) emissions for Brazil and China from 2000 to 2016. Design/methodology/approach – The input-output method apply to multiregional tables from Eora-26 to decompose the GHG emissions of the Brazilian and Chinese productive structure. Findings – The data reveals that Chinese production and consumption emissions are associated with power generation and energy-intensive industries, a significant concern among national and international policymakers. For Brazil, the largest territorial emissions captured by the metrics come from services and traditional industry, which reveals room for improving energy efficiency. The analysis sought to emphasize how the productive structure and dynamics of international trade have repercussions on the environmental dimension, to promote arguments that guide the execution of a more sustainable, productive and commercial development strategy and offer inputs to advance discussions on the attribution of climate responsibility. Research limitations/implications – The metrics did not capture emissions related to land use and deforestation, which are representative of Brazilian emissions. Originality/value – Comparative analysis of emissions embodied in traditional sectoral trade flows and GVC, on backward and forward sides, for developing countries with the main economic regions of the world.